(untitled) (Research, Society and Development, 2022)
The purpose of this essay is to work on the issue of the administrator’s responsibility in the face of business failure. In this way, the study is aimed at discussing issues related to aspects of civil and administrative responsibility based on the analysis of the duty of diligence, focusing on the case of Empresa Sadia LTDA. The analysis of this problem is of paramount importance since it brings into focus the discussion about the civil and administrative responsibility of the administrator when he does not fulfill his fiduciary duties, which entails consequences for the social, economic and legal reality. In this context, the objective is to verify the impacts that the CVM’s decision in the Sadia case had on the administrator’s performance regarding his accountability. The methodology used consists of applied research, with a deductive and qualitative approach, with a descriptive objective, with the purpose of proposing formative evaluation. It is concluded that, as much as the Brazilian Corporate Law provides protection to administrators, they do not have the power to exempt themselves from responsibility, when present the non-compliance with the duties inherent to the activity.